Factors that influence the customer’s acceptance of Islamic Bank: A study on Bank Islam Malaysia Berhad Kota Bharu, Kelantan / Nik Ayesha Syakira Nik Mohammed Ainul Azlan - Nik Mohammed Ainul Azlan, Nik Ayesha Syakira (2015)
This paper aimed to identify the vital factors that have contributed to the growth of the Islamic banking. Islamic banking was established in Malaysia since 1983. To date, Islamic banking products are available at two full pledged Islamic banks and at all commercial and merchant banks in Malaysia. At the end of 2000, total deposit at conventional banks was RM381 billion while total deposit in Islamic system was RM31 billion. This study focuses on the factors influencing the customer acceptance of Islamic Bank at Bank Islam Malaysia Berhad (BIMB), Kota Bharu. Several identifiable variables were selected concerning religious perspective, quality of services and availability of services in measuring its contribution to the acceptance of customer towards BIMB. Using questionnaire as research instrument, 90 sets of questionnaires had been distributed to the customer at BIMB, Jalan Sultan Ibrahim Branch, Kota Bharu. The sample was analysed through judgement sampling from the total number of account holders of Bank Islam customer’s. The result of the investigation demonstrated that all the identifiable constructs were substantial to strong and significantly correlated with the customer acceptance towards Bank Islam, Jalan Sultan Ibrahim Branch, Kota Bharu